Psychometric properties of the Opening Minds Stigma Scale for Health Care Providers in 32 European countries – A bifactor ESEM representation - Őri, Dorottya; Szocsics, Péter; Molnár, Tamás; Bankovska Motlova, Lucie; Kazakova, Olga; Mörkl, Sabrina; Wallies, Michael; Abdulhakim, Mohamed; Boivin, Sylvie; Bruna, Krista; Cabacos, Carolina; Carbone, Elvira Anna; et al. (Frontiers in Public Health, 2023)
Aims To measure the stigma of healthcare providers toward people suffering from mental illness, the Opening Minds Stigma Scale for Health Care Providers (OMS-HC) is a commonly applied instrument. However, this scale has not been thoroughly validated in many European countries, its psychometric properties are still unknown and data on practicing psychiatrists is lacking. Therefore, this multicenter study aimed to assess the psychometric characteristics of the 15-item OMS-HC in trainees and specialists in adult and child psychiatry in 32 countries across Europe. Material and methods The OMS-HC was conducted as an anonymous online survey and sent via Email to European adult and child psychiatrists. Parallel analysis was used to estimate the number of OMS-HC dimensions. Separate for each country, the bifactor ESEM, a bifactor exploratory structural equation modeling approach, was applied to investigate the factor structure of the scale. Cross-cultural validation was done based on multigroup confirmatory factor analyses and reliability measures. Results A total of 4245 practitioners were included, 2826 (67%) female, 1389 (33%) male. The majority (66%) of participants were specialists, with 78% working in adult psychiatry. When country data were analyzed separately, the bifactor model (higher-order factor solution with a general factor and three specific factors) showed the best model fit (for the total sample χ2/df=9.760, RMSEA=0.045 (0.042-0.049), CFI=0.981; TLI=0.960, WRMR=1.200). The average proportion of variance explained by the general factor was high (ECV=0.682). This suggests that the aspects of ‘attitude’, ‘disclosure and help-seeking’, and ‘social distance’ could be treated as a single dimension of stigma. Among the specific factors, the ‘disclosure and help-seeking’ factor explained a considerable unique proportion of variance in the observed scores. Conclusions This international study has led to cross-cultural analysis of the OMS-HC on a large sample of practicing psychiatrists. The bifactor structure displayed the best overall model fit in each country. Rather than using the subscales, we recommend the total score to quantify the overall stigmatizing attitudes. Further studies are required to strengthen our findings in countries where the proposed model was found to be weak.